HUBUNGAN ANTARA KEPERCAYAAN INTERPERSONAL DENGAN PEMAAFAN PADA INDIVIDU BERPACARAN DI KECAMATAN GADINGREJO - Dwi Kumala, Sefia; Muhammad Lathief Syaifussalam (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Conflict often occurs in romantic relationships during early adulthood, which can lead to relationship failure. Forgiveness is an essential component in repairing romantic relationships affected by conflict. One factor that may influence an individual's willingness to forgive is the quality of the relationship, particularly the presence of interpersonal trust. The aim of this study is to examine the relationship between interpersonal trust and forgiveness among dating individuals in the Gadingrejo District. This study employed a quantitative research method and used purposive sampling to select participants. The sample consisted of 392 individuals currently in romantic relationships, residing in the Gadingrejo District. Data were analyzed using the Spearman Rho correlation technique, which revealed a highly significant negative relationship, with a correlation coefficient of -0.459 and p = 0.000 (p < 0.001). This indicates that the higher the level of interpersonal trust, the lower the level of forgiveness toward one's partner. Interpersonal trust contributed an effective value of 10.9% to forgiveness.